Telomerase activity, relative telomere length, and longevity in alfalfa (Medicago sativa L.) - A,Yun; Shi,Shangli; Sun,Shoujiang; Jing,Yuanyuan; Li,Zili; Zhang,Xiaoyan; Li,Xiaolong; Wu,Fang (PeerJ, 2022)
Background Medicago sativa L. ‘Qingshui’ is a valuable rhizomatous forage germplasm resource. We previously crossed Qingshui with the high-yielding Medicago sativa L. ‘WL168’ and obtained novel rhizomatous hybrid strains (RSA-01, RSA-02, and RSA-03). Telomere dynamics are more accurate predictors of survival and mortality than chronological age. Based on telomere analyses, we aimed to identify alfalfa varieties with increased stamina and longevity for the establishment of artificial grazing grasslands. Methods In this study, we performed longitudinal analysis of telomerase activity and relative telomere length in five alfalfa varieties (Qingshui, WL168, RSA-01, RSA-02, and RSA-03) at the age of 1 year and 5 years to examine the relationship among telomerase activity, rate of change in relative telomere length, and longevity. We further aimed to evaluate the longevity of the examined varieties. Telomerase activity and relative telomere length were measured using enzyme-linked immunosorbent assay and real-time polymerase chain reaction, respectively. Results We observed significant differences in telomerase activity between plants aged 1 year and those aged 5 years in all varieties except WL168, and the rate of change in telomerase activity does not differ reliably with age. As telomerase activity and relative telomere length are complex phenomena, further studies examining the molecular mechanisms of telomere-related proteins are needed. Relative telomere lengths of Qingshui, WL168, RSA-01, RSA-02, and RSA-03 in plants aged 5 years were higher than those aged 1 year by 11.41, 11.24, 9.21, 10.23, and 11.41, respectively. Relative telomere length of alfalfa tended to increase with age. Accordingly, alfalfa varieties can be classified according to rate of change in relative telomere length as long-lived (Qingshui, WL168, and RSA-03), medium-lived (RSA-02) and short-lived (RSA-01). The differences in relative telomere length distances of Qingshui, WL168, RSA-01, RSA-02, and RSA-03 between plants aged 1 and 5 years were 10.40, 13.02, 12.22, 11.22, and 13.25, respectively. The largest difference in relative telomere length was found between Qingshui and RSA-02 at 2.20. Our findings demonstrated that relative telomere length in alfalfa is influenced by genetic variation and age, with age exerting a greater effect.
Keywords: Alfalfa; Telomerase activity; Relative telomere length; Longevity; Aging